Effect of intercropping hybrid poplar and switchgrass on biomass yield, forage quality, and land use efficiency for bioenergy production. (April 2018) - Kimura, Emi; Fransen, Steven C.; Collins, Harold P.; Stanton, Brian J.; Himes, Austin; Smith, Jeffrey; Guy, Stephen O.; Johnston, William J.
Abstract: Land use efficiency can be maximized if an intercropping system is utilized to produce switchgrass ( Panicum virgatum L.) biomass within the alleys between hybrid poplar trees ( Populus spp.). Information is limited on switchgrass production and intercropping system in the Pacific Northwest of U.S. The objectives of this study were to evaluate the effects of hybrid poplar trees on switchgrass yield and forage quality and to determine the land use efficiency in an intercropping system under irrigation. Three cultivars of switchgrass ('Kanlow', 'Blackwell', and 'Trailblazer') were planted in the alleys between hybrid poplar trees (Clones: OP367 and PC4) at the Greenwood Resources, Boardman, OR in 2011. Switchgrass growth was negatively influenced by hybrid poplar trees with mean leaf area index, tiller density, and switchgrass dry matter (DM) yield in the monoculture and intercropped plots equal to 4.9 and 1.7, 383 and 69 tillers m −2, and 15 and 4 Mg ha −1, respectively, in the third year of this study. The 3-year cumulative switchgrass monoculture, switchgrass intercropping, and tree yield was 47.7, 21.5, and 58.5 Mg ha −1 . As a result, cumulative land equivalent ratio during the three years of the study was 1.45 in intercropped compared to 1.0 in monoculture plots. This indicates that 45% more land would be required in monoculture system to produce the same amount of DM produced in the intercropping system. This study revealed that, despite the reduced switchgrass growth under hybrid poplar trees, intercropping hybrid poplar and switchgrass can improve land use efficiency for biomass production. Highlights: Effects of intercropping hybrid poplar and switchgrass on yield, forage quality, and land use efficiency were proposed. Switchgrass growth decreased in terms of leaf area index, tiller density, and dry matter yield. Land use efficiency was greater in the intercropped than monoculture plots regardless of the reduced switchgrass growth.